Strategy for Implementing Operations to Handle the Crime of Narcotics - Arif Purnama Oktora; Hilaire Tegnan (Journal of Human Rights, Culture and Legal System, 2021)
Narcotics abuse is closely related to illicit trafficking as part of trans national organized crime. People become dependent so that the supply continues to increase. The relationship between dealers and victims is solidly bonded. It is difficult for victims to escape from dealer/s, even though victims are not frequently involved. This solid relationship between dealer/s and victim/s put the police in difficulty overcoming the crime. However, the West Jakarta Metro Police successfully manages to tackle that challenge. This research takes place in the West Jakarta Police Station. This article aims to explain the strategy for handling the 120 kg narcotics crimes by the West Jakarta Metro Police. The results of this study indicate that the attainment of the West Jakarta Metro Police depends on four things: (1) the pungent substance of the law on narcotics; (2) adequate law enforcement; (3) strategic programs in improving the competence of components of investigators; and (4) the existence of institution facilities and structures that support the case handling process.